Correlation Between Circulating PCSK9 Levels and Gestational Diabetes Mellitus in a Chinese Population - Wu, Yiming; Shi, Jie; Su, Qing; Yang, Zhen; Qin, Li (Frontiers in Endocrinology, 2022)
Background: Proprotein convertase subtilisin/kexin type 9 (PCSK9) has been demonstrated to be involved in not only lipid metabolism but also glucose homeostasis. The aim of this study was to estimate the levels of circulating PCSK9 in subjects with gestational diabetes mellitus (GDM) and investigate the relationships between PCSK9 and related metabolic phenotypes in GDM. Methods: Circulating PCSK9 levels were measured by ELISA kit in 130 women with GDM and 170 normal glucose tolerance (NGT) pregnant women. Blood samples were collected to detect Biochemical indexes in all participants. Diagnosis of GDM was made according to the International Association of the Diabetes and Pregnancy Study Groups Consensus Panel. Correlation analysis and logistic regression analysis were performed to detect the potential relationship between PCSK9 levels and GDM. Results: Circulating PCSK9 levels were significantly higher in the GDM group than that in the NGT pregnant group, (268.07±77.17 vs. 254.24±74.22 ng/ml, p<0.05). In GDM group, serum PCSK9 levels were positively correlated with fasting plasma glucose (FPG) (R=0.251, P=0.015), glycosylated hemoglobin (HbA1c) (R=0.275, P=0.009), total cholesterol (TC) (R=0.273, P=0.010) and low-density lipoprotein cholesterol (LDL-C) (R=0.326, P=0.002) after adjustment of age and gestational age. Logistic regression showed that age (OR=5.412, P=0.02) as well as serum PCSK9 levels (OR=4.696, P=0.03) were the independent risk factors of GDM. Compared with the lowest serum PCSK9 levels quartile group, the risk of GDM was significantly higher in the highest quartile group, the ORs of GDM were 3.559 (95%CI 1.346-9.416, p< 0. 01 for the trend), after adjusting for potential cofounder. Conclusions: Elevated circulating PCSK9 levels are associated with an increased incidence of gestational diabetes mellitus indicating a potential role of PCSK9 in GDM.